Auditing Risks: An Integrated or Separate Assessment (Evidence from Iran) - Nikoomaram, Hashem; Roodposhti, Fraydoon Rahnama; Hajiha, Zohreh (JABM, 2010)
This study examines the relationship between inherent risk and control risk, by referring to Risk Based Audit (RBA). We divided these risks to sub categories and allocated the affecting factors on risks to each sub category based on prior literature and then examined the relationships between any sub categories of these risks. We also examined whether Iranian independent auditors prefer to asses these risks as two separate risks, as Audit Risk Model proposed, or to assess them as an integrated risk as Risk of Material Misstatement. The first point toward Risk Based Audit approach is to clarify the overall risk that auditor can accept when presenting audit opinion. However, prior studies indicate that there is a strong correlation between inherent and control risks, professional standards require no single method to assess these risks. The statistical sample of the research consists of 64 senior auditors. We presented 48 affecting critical factors in two categories in inherent risk and four categories in control risk to auditors and measured the significance degree of each affecting factor on inherent and control risks via questionnaire. The results of descriptive statistics and Pearson correlation indicate that there are no significant relationships between inherent and control risks totally, although some correlations were observed between some sub categories. Additionally, the assessment of risks separately is preferred to an integrated assessment. Hence, our results suggest that separate assessment of inherent and control risks seems to be more relevant and informative, as independent auditors prefer to act in practice.